(3GfYcGSGJgG hcjajI GdJYGed eYgGs - (3aVd Gddg eMeO(B, (3SdWMs ((3GdGScfOQjI(B:s (3ecJHI HSJGf GdeYQaI(B,s, 2002)
(3aj gPG GdcJGH (B: (3eaghe GdYhdeI, gd ddYhdeI CUhd JGQNjI aj GdacQ GdadSaj, gd ddYhdeI EfYcGSGJ Ydi Ohd GdYGde GdKGdK, OhQ GdCee GdeJMOI aj Xd fXGe GdYhdeI ,NGJeI JhVM EdbGA GdVhA Ydi NWhQI GdYhdeI hcjajI GdJYGed eYgGs
Keywords: (3GdYhdeI (B-(3GdJGQjNs